The Authority of the Special Guidance for Children in Gorontalo City, Gorontalo Province in Implementing Guidance for Children in Conflict with the Law - Leni Nurmala (IHSA Institute, 2022)
In the Juvenile Criminal Justice System, the Child Special Guidance Institution (LPKA) is a forum for children to carry out their criminal period. As the next generation, children have an important position so they must get protection and guarantees for their rights. In this article, the author limits the discussion of the role of LPKA in providing guidance to children in conflict with the law. The sociological juridical research method is used with the aim of obtaining empirical legal knowledge obtained directly from the object. The implementation of special guidance for children in conflict with the law is guided by Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The role of LPKA is to provide guidance and supervision to children in carrying out their criminal sanctions. The results of research and discussion obtained at the Gorontalo City Children's Special Guidance Institute, children receive guidance and education. Coaching activities are carried out to shape the personality in the form of developing the potential of children according to the needs and conditions of children, while educational/school activities cooperate with the relevant education office. Children in conflict with the law can become good individuals and can face the future brilliantly.